Religious, Feminist, Activist : Cosmologies of Interconnection - Zwissler, Laurel (Book collections on Project MUSE., 2018)
"In Religious, Feminist, Activist, Laurel Zwissler investigates the political and religious identities of women who understand their social-justice activism as religiously motivated. Placing these women in historical context as faith-based activists for social change, this book discusses what their activities reveal about the public significance of religion in the pluralistic context of North America and in our increasingly globalized world. Zwissler's ethnographic interviews with feminist Catholics, Pagans, and United Church Protestants reveal radically different views of religious and political expression and illuminate how individual women and their communities negotiate issues of personal identity, spirituality, and political responsibility. Political activists of faith recount adventurous tales of run-ins with police, agonizing moments of fear and powerlessness in the face of global inequality, touching moments of community support, and successful projects that improve the lives of others. Religious, Feminist, Activist combines religion, politics, and globalization--subjects frequently discussed in macro terms--with individual personalities and intimate stories to provide a fresh perspective on what it means to be religiously and politically engaged. Zwissler also provides an insightful investigation into how religion and politics intersect for women on the political left."